2013
DOI: 10.1371/journal.pone.0068346
|View full text |Cite
|
Sign up to set email alerts
|

Cenderitide-Eluting Film for Potential Cardiac Patch Applications

Abstract: Cenderitide, also known as CD-NP, is a designer peptide developed by combining native mammalian c-type natriuretic peptide (CNP) and the C-terminus isolated from the dendroapis natriuretic peptide (DNP) of the venom from the green mamba. In early studies, intravenous and subcutaneous infusion of cenderitide was reported to reduce left ventricular (LV) mass and ameliorate cardiac remodelling. In this work, biodegradable polymeric films encapsulating CD-NP were developed and were investigated for their in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…CD-NP in vitro activated cGMP and suppressed cell proliferation of human cardiac fibroblasts induced by cardiotrophin-1 (a marker of HF and myocardial infarction) [104]. Recent research has proposed that CD-NP-eluting polymeric films may eventually be employed as cardiac patches which, via local application, could be used to suppress cardiac remodeling and fibrosis [108]. The first clinical trial in healthy human volunteers reported that CD-NP was well tolerated and activated cGMP, induced natriuresis, and suppressed aldosterone without causing excessive hypotension [109].…”
Section: Cd-natriuretic Peptide (Or Cenderitide)mentioning
confidence: 99%
“…CD-NP in vitro activated cGMP and suppressed cell proliferation of human cardiac fibroblasts induced by cardiotrophin-1 (a marker of HF and myocardial infarction) [104]. Recent research has proposed that CD-NP-eluting polymeric films may eventually be employed as cardiac patches which, via local application, could be used to suppress cardiac remodeling and fibrosis [108]. The first clinical trial in healthy human volunteers reported that CD-NP was well tolerated and activated cGMP, induced natriuresis, and suppressed aldosterone without causing excessive hypotension [109].…”
Section: Cd-natriuretic Peptide (Or Cenderitide)mentioning
confidence: 99%
“…Currently, CD‐NP is undergoing initial evaluation in humans by Mayo Clinic to address ventricular remodeling. Our previous work have also demonstrated that controlled release of CD‐NP from films and patches sustained the suppression of human cardiac fibroblast proliferation for cardiac remodeling indication . However, its utility as an antirestenotic compound have not yet been tested.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental models of cardiovascular disease, novel nanoparticle gel polymer strategies are being tested [44]. Further, a novel film delivery system in which Cenderitide is released from a patch-like device around the heart is also being tested [45]. An oral delivery platform is favored but remains a challenge to achieve acceptable levels of bioavailability.…”
Section: Cenderitide (Cd-np) For Heart Failure: Clinical Studiesmentioning
confidence: 99%